2019
DOI: 10.1016/j.semradonc.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Adaptive Radiation Therapy (ART): Conceptual Considerations for the Informed Clinician

Abstract: For nearly two decades, adaptive radiation therapy (ART) has been proposed as a method to account for changes in head and neck tumor and normal tissue to enhance therapeutic ratios. While technical advances in imaging, planning and delivery have allowed greater capacity for ART delivery, and a series of dosimetric explorations have consistently shown capacity for improvement, there remains a paucity of clinical trials demonstrating the utility of ART. Furthermore, while ad hoc implementation of head and neck A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 143 publications
1
77
0
5
Order By: Relevance
“…Notwithstanding the refinement of IMRT techniques in planning optimization, on the whole no specific constraints for the skin are available in the clinic, nor are indications on how to contour it in the irradiated area, nor are suggestions on how much should the PTV be cropped off the patient's external surface. In addition, no high‐level evidence mandates the need of adaptive replanning on a routine basis in case of weight loss or tumor shrinkage, events that frequently occur in patients undergoing chemo‐radiation for HNSCC. However, in these cases the risk of relative skin overdosage should be closely monitored: A pilot prospective study on 20 patients demonstrated that by adapting the dose distribution with a new plan from the fourth week of radiation the skin surface receiving >50 Gy could be significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the refinement of IMRT techniques in planning optimization, on the whole no specific constraints for the skin are available in the clinic, nor are indications on how to contour it in the irradiated area, nor are suggestions on how much should the PTV be cropped off the patient's external surface. In addition, no high‐level evidence mandates the need of adaptive replanning on a routine basis in case of weight loss or tumor shrinkage, events that frequently occur in patients undergoing chemo‐radiation for HNSCC. However, in these cases the risk of relative skin overdosage should be closely monitored: A pilot prospective study on 20 patients demonstrated that by adapting the dose distribution with a new plan from the fourth week of radiation the skin surface receiving >50 Gy could be significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive Radiation Therapy is becoming more prevalent in RT practice, and is inherently reliant upon departmental IGRT protocols. A comprehensive discussion of ART is beyond the scope of this paper but has been well-covered by recent reviews [107,108]. The growing body of ART literature does however provide an insight into when volumetric changes are likely to be detected that merit replanning during the treatment course.…”
Section: D Igrt Volume Changes and Adaptive Radiation Therapy (Art)mentioning
confidence: 99%
“…In contrast to traditional 'offline' ART strategies that involve replanning between fractions, 'online' ART enables plan adaption in response to daily volumetric changes while the patient remains on the treatment couch prior to treatment delivery [112]. Though still an emerging technology with limited clinical data available, online ART is commercially available with both MR-and CBCTbased treatment platforms [107]. Such systems represent a paradigm shift from linear workflow of conventional RT for RTTs at the treatment console, merging treatment planning with established practices in online IGRT [107,108].…”
Section: D Igrt Volume Changes and Adaptive Radiation Therapy (Art)mentioning
confidence: 99%
See 1 more Smart Citation
“…Use of magnetic resonance imaging (MRI) rather than computed tomography (CT) for radiotherapy (RT) planning can be highly desirable because MRI visualizes soft tissues with superior contrast and resolution (1), introduces unique sequences and contrast agents for delineating specific tumors and anatomic subsites (1, 2), and permits daily adaptive radiotherapy (ART) without added CT radiation dose (35). MRI-guided ART (MRIgART) machines have advanced from low-field (0.35 Tesla) magnets with Cobalt-60 radiation sources (6) to diagnostic-strength magnetic fields (1.5 Tesla) fully integrated with linear accelerators (7, 8) in <5 years.…”
Section: Introductionmentioning
confidence: 99%